2019
DOI: 10.1002/jctb.6164
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of glucocorticoids in water by dielectric barrier discharge and dielectric barrier discharge combined with calcium peroxide: performance comparison and synergistic effects

Abstract: BACKGROUND: Degradation of glucocorticoids (GCs), including fluocinolone acetonide (FA), triamcinolone acetonide (TA) and clobetasol propionate (CP), in water by dielectric barrier discharge (DBD) and DBD combined with calcium peroxide treatment (DBD/CaO 2 ) were investigated. Effects of discharge power, pH, plasma-working gas and CaO 2 dosage were examined during DBD and DBD/CaO 2 treatments. The synergistic output from the combination of CaO 2 with DBD on •OH concentration, pH, conductivity, CaO 2 adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Among these, multi-pin corona discharge system has been proposed as an appropriate reactor to improve the discharge energy density requiring a lower voltage for the discharge formation [35]. In addition, several novelties have been also introduced to maximize the energy efficiency of plasma processes including the use of innovative power sources, especially those based on nanosecond pulsed generators [36][37][38], or the supplementary use of catalysts/additives to boost the generation of the reactive species [38][39][40][41]. Nevertheless, the use of catalysts introduces extra costs and recovery steps.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, multi-pin corona discharge system has been proposed as an appropriate reactor to improve the discharge energy density requiring a lower voltage for the discharge formation [35]. In addition, several novelties have been also introduced to maximize the energy efficiency of plasma processes including the use of innovative power sources, especially those based on nanosecond pulsed generators [36][37][38], or the supplementary use of catalysts/additives to boost the generation of the reactive species [38][39][40][41]. Nevertheless, the use of catalysts introduces extra costs and recovery steps.…”
Section: Introductionmentioning
confidence: 99%
“… Approach Substance E EO Operating cost a Ref. (kWh L −1 ) ($ L −1 ) DBD glucocorticoids 32.28 4.69 [5] DBD/CaO 2 glucocorticoids 18.28 2.65 [19] DBD 2, 4-dichlorophenol 4.83 0.70 [47] Microplasma organophosphorus 0.56 0.08 [67] Microplasma organochlorine 2.56 0.37 [67] Photo-Fenton terbutryn, chlorfenvinphos, pentachloro-phenol , and diclofenac 31.47 4.57 [68] Photo-Fenton micropollutant 0.17 0.02 [31] PBCD glucocorticoids 1.39 0.20 this study PBCD/ACF glucocorticoids 0.76 0.11 this study PBCD/Fe-ACF glucocorticoids 0.38 0.05 this study a The European Union currently maintains an average industrial electricity price of US $0.15/ kWh [69] . …”
Section: Resultsmentioning
confidence: 99%
“…Major types of NTP reactors include corona discharge (CD), dielectric barrier discharge (DBD), arc discharge (AC) and contact glow discharge electrolysis (CGDE) [18] . Our previous study reported that GCs could be efficiently degraded by DBD [19] . However, energy consumption and mass transfer efficiency at the gas-liquid interface are the main factors limiting its expansion [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation